Conventional and microwave pyrolysis remediation of crude oil contaminated soil - Ogunkeyede, Akinyemi Olufemi (2016)
The Nigerian economy has relied heavily on crude oil production since independence in 1960. As a consequence, it has seen an influx of multinational petroleum companies with oil exploration and associated activities having significant environmental impacts, particularly oil leakage and spillage into soil and the overall degradation of the ecosystem in the Niger Delta area. This study aims to find a viable solution to the remediation of polluted soil by comparing two thermal remediation techniques, namely microwave pyrolysis and traditional pyrolysis, which has been investigated using a Gray-King retort. The polluted soil was first examined to ascertain the distribution of the soil organic carbon (SOC) with 78% found to be solvent extractable in dichloromethane/methanol, while 95 % was thermally labile and removed under hydropyrolysis (HyPy) conditions at 550 °C. The remaining 5 % of the SOC was composed of a recalcitrant residue being defined as the black or stable polyaromatic carbon fraction. The solvent extractable organic matter (EOM) was then further separated into the maltene (free phase) and asphaltene (bound phase) fractions together for comparison with a sample of Nigerian crude oil provided by the Shell Petroleum Development Company (SPDC), Nigeria. The Nigerian crude oil is a light crude oil with the percentage of maltene (95.2 %) was far higher than the asphaltene (4.8 %). A closer margin was observed in the percentage between the maltene (88.3 %) and asphaltene (11.7 %) in the soil EOM due to biodegradation. The biomarker profile of the EOM was compared with that of a Nigerian crude oil to confirm that the EOM contains the crude oil in the soil. Their biomarker profiles revealed that the source inputs were terrigenous from deltaic settings, of Late Upper Cretaceous age and deposited under oxic conditions. Oleanane (a pentacyclic triterpene, abundant in oils from the Niger Delta) was present in both the crude oil and EOM and the hopane and the sterane distributions (m/z 191 and m/z 217 respectively) were similar in every respect, which indicates that the probable source of the pollutant crude oil in the soil is similar in composition to the Nigerian crude oil. Accordingly, the polluted soil was treated with microwave pyrolysis and Gray-King pyrolysis to remove the crude oil pollutant. The maximum average recovered products from the thermal remediation process with Gray-King pyrolysis is 99.4 % TOC and maximum crude oil pollutant removed by Gray-King pyrolysis was 85.3 % TOC with maximum oil recovery of 70 % TOC from all the different treatment conditions, while the shortest treatment time condition gave the lowest gas yield of 10.2 % TOC. This implies that 100 % removal with respect to EOM and 89 % removal with respect to HyPy as discussed above. Furthermore, the polluted soil was also treated with microwave pyrolysis with maximum pollutant removal of 77 % TOC, which is 98.7 % removal with respect to EOM and 81 % with respect to HyPy. In conclusion, Gray-King pyrolysis removed more of the soil organic carbon than microwave pyrolysis, but the latter does have advantages regarding operability and greater output within a short treatment time.